Nilai Ekologis dalam Peribahasa Madura; Kajian Hermeneutik - Moh. Hafid Effendy; Suhanda Suhanda (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
This research aims to describe the meaning of Madurese proverbs that contain ecological values. The research method used is qualitative with a hermeneutic approach. The source of data on proverbs was obtained from a documented study of Oemar Sastrodiwirdjo’s collection of proverbs and saloka. Data analysis was conducted using in-depth knowledge in accordance with the hermeneutic circle. This analysis was carried out hermeneutically with an interactive dialectical model. The research findings show that ecological values in Madurese proverbs include four forms of value: relational values in proverbs that relate to nature, spiritual values in proverbs that relate to the attributes of God, aesthetic values in proverbs that relate to the physical qualities of women, and educational ecological values in proverbs about nature as a source of learning to develop character